2021
DOI: 10.3390/cancers13020168
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Baseline Clinical Characteristics and Biomarkers Associated with Outcome in Advanced Melanoma Patients Treated with Pembrolizumab

Abstract: Background: Pembrolizumab improves the survival of patients with advanced melanoma. A comprehensive analysis of baseline variables that predict the benefit of pembrolizumab monotherapy has not been conducted. Methods: Survival data of patients with advanced melanoma who were treated with pembrolizumab in a single university hospital were collected. A multivariate Cox regression analysis was performed to correlate baseline clinical, laboratory, and radiologic characteristics and NanoString IO360 gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 31 publications
(49 reference statements)
6
35
1
Order By: Relevance
“…Prior studies of melanoma patients, received targeted therapies, identified the number of metastatic organ sites or the number of lesions along with baseline LDH level as predictive factors for PFS and OS [42,43]. Our findings also indicated that the total number of metastatic lesions and their numbers in the abdomen and pelvis in the 3-month follow-up scan were among the fourteen most predictive values for the 5-year survival rate.…”
Section: Tablesupporting
confidence: 59%
“…Prior studies of melanoma patients, received targeted therapies, identified the number of metastatic organ sites or the number of lesions along with baseline LDH level as predictive factors for PFS and OS [42,43]. Our findings also indicated that the total number of metastatic lesions and their numbers in the abdomen and pelvis in the 3-month follow-up scan were among the fourteen most predictive values for the 5-year survival rate.…”
Section: Tablesupporting
confidence: 59%
“…Considering the influence of gender [ 43 ] and the number of metastasis [ 44 ], our analysis showed no differences in the percentage of PD1 + EVs with the only exception of those released by DCs which showed a slight increase in responders vs non-responders. Conversely, if we consider the possible correlation between PD1 + EVs and these two parameters as a function of the response to immunotherapy, we always found a notable increase in PD1 + EVs in the plasma of the non-responders of both subgroups (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Also, high LDH levels, the number of metastatic sites, and previous treatment with systemic therapies have a negative effect. Other biochemical and immunohistochemical analyses are being studied to determine their capability to predict response to ICI and therefore outcome [9]. Our aim was to demonstrate whether changes in metabolic tumor volume assessed by FDG-PET/CT could be used to predict the long-term efficacy of Pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship has already been demonstrated between outcome and various clinical factors such as certain previous treatments (for example Ipilimumab and BRAF-/MEK-inhibitors), presence of brain metastases, and the number of metastatic locations. Immunohistochemical analysis also shows promising results for the prediction of outcomes [9].…”
Section: Introductionmentioning
confidence: 99%